Analisis Efisiensi Motor Induksi Tiga Phasa Rotor Sangkar Dengan Kondisi Pembebanan Yang Berbeda - Rusman Rusman; Suparno; Taufik Muzakkir (Jurnal ELIT, 2026)
Three-phase induction motors are AC electric motors widely used in both industry and household applications. Over time, these motors experience a decline in performance, including a reduction in torque and efficiency due to the deterioration of material resistance. One of the challenges in measuring the efficiency of induction motors during operation is the difficulty in measuring the motor's output parameters without disconnecting the motor from its load. This study aims to provide an alternative solution for measuring the efficiency of three-phase induction motors while they are in operation in industrial settings. The method used involves calculating the load as a percentage of the motor's rated output capacity, followed by current load estimation using the Line Current Measurement method. A digital power meter, LCD module for data display, and PLC as a control device were employed for monitoring. The study was conducted on a 1.1 kW three-phase induction motor, tested in the Electrical Engineering Laboratory at POLNEP. The results show that the developed measurement device can monitor the motor's parameters and display efficiency in real-time. The accuracy of the device is good within the load range of 65% to 76% of the rated capacity, but decreases at lower load levels. Comparison between the measured values and theoretical calculations indicates a low margin of error at specific load ranges, with the error increasing as the load decreases. The optimal load range for the motor is between 60% and 80% of its rated capacity.